Ὁ Νικόλας Γύζης στὴ Μικρὰ Ἀσία (1873) - Παυλόπουλος, Δημήτρης (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2015)
In 1873, the great Greek painter Nikolas Gyzis (1842-1901), together with Nikiforos Lytras (1832-1904), professor of Painting at the School of Fine Arts in Athens, travelled in Asia Minor, in the broader context of the cultural influence of Orientalism in Europe. To mark the anniversary of the completion of one hundred and forty years (2013) from this journey, in this article we discuss the genre works and landscapes oil paintings and pencil sketches from Gyzis’s journey in Asia Minor.